2021
DOI: 10.1093/bjs/znab220
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound screening for abdominal aortic aneurysm in high-risk women

Abstract: Background Population-wide ultrasound screening programmes for abdominal aortic aneurysm (AAA) for men have already been established in some countries. Women account for one third of aneurysm-related mortality and are four times more likely to experience an AAA rupture than men. Whole-population screening for AAA in women is unlikely to be clinically or economically effective. The aim of this study was to determine the outcomes of a targeted AAA screening programme for women at high risk of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The recently published Female Aneurysm Screening Study (FAST) from Leicester (2021) which adopted targeted screening approach for women (aged 65-74 years) with high risk factors (smoking or/and heart disease), concluded that in the population who attended screening, the prevalence of AAA among women with cardiovascular disease was 0.29% for AAA which is much lower than expected 0.35%, above which AAA screening seems to be effective. 37 A retrospective cohort study from France suggested ultrasound screening in women, especially with a positive family history where a first-degree relative is affected, has a prevalence of AAA in this cohort of 8.3%. 38 There are varying perspectives on recommendations for screening first degree relatives with regards to their age and sex.…”
Section: Familial Aaamentioning
confidence: 84%
“…The recently published Female Aneurysm Screening Study (FAST) from Leicester (2021) which adopted targeted screening approach for women (aged 65-74 years) with high risk factors (smoking or/and heart disease), concluded that in the population who attended screening, the prevalence of AAA among women with cardiovascular disease was 0.29% for AAA which is much lower than expected 0.35%, above which AAA screening seems to be effective. 37 A retrospective cohort study from France suggested ultrasound screening in women, especially with a positive family history where a first-degree relative is affected, has a prevalence of AAA in this cohort of 8.3%. 38 There are varying perspectives on recommendations for screening first degree relatives with regards to their age and sex.…”
Section: Familial Aaamentioning
confidence: 84%
“…AAA is less common in women in the general population; however, this may be due to the fact that AAA in women is still underdiagnosed and undertreated. However women with AAA are now four times more likely to have a ruptured AAA compared to men of the same age and account for one third of deaths due to AAA ruptures [14]. Van de Luijtgaarden et al [15] examined patients with AAA invited to the multidisciplinary vascular/genetics outpatient clinic between 2009 and 2012 for an assessment of family history using questionnaires.…”
Section: Epidemiologymentioning
confidence: 99%
“…15,18 Another recent trial of ultrasound screening in 5200 high-risk women ages 65 to 74 years found an AAA incidence of 0.29% (95% CI, 0.18%-0.48%) in which only 3 large aneurysms were identified. 22 In the United States, rates of screening for AAA remain low. 23 One study has shown electronic medical record-based reminders increased screening rates from 48% to 80%.…”
Section: Aneurysm Sizementioning
confidence: 99%